Role of Sleep Restriction in Daily Rhythms of Expression of Hypothalamic Core Clock Genes in Mice - Weitian Li; Zixu Wang; Jing Cao; Yulan Dong; Yaoxing Chen (Current Issues in Molecular Biology, 2022)
Lack of sleep time is a menace to modern people, and it leads to chronic diseases and mental illnesses. Circadian processes control sleep, but little is known about how sleep affects the circadian system. Therefore, we performed a 28-day sleep restriction (SR) treatment in mice. Sleep restriction disrupted the clock genes’ circadian rhythm. The circadian rhythms of the Cry1 and Per1/2/3 genes disappeared. The acrophase of the clock genes (Bmal1, Clock, Rev-erbα, and Rorβ) that still had a circadian rhythm was advanced, while the acrophase of negative clock gene Cry2 was delayed. Clock genes’ upstream signals ERK and EIFs also had circadian rhythm disorders. Accompanied by changes in the central oscillator, the plasma output signal (melatonin, corticosterone, IL-6, and TNF-α) had an advanced acrophase. While the melatonin mesor was decreased, the corticosterone, IL-6, and TNF-α mesor was increased. Our results indicated that chronic sleep loss could disrupt the circadian rhythm of the central clock through ERK and EIFs and affect the output signal downstream of the core biological clock.